Kebijakan Konservasi Air Suci dalam Menjaga Kelangsungan Agama Hindu di Desa Mas Kecamatan Ubud Kabupaten Gianyar - Mahardhika, I Putu Eka (Sphatika: Jurnal Teologi, 2023)
Beji Temple in the context of conveying the socio-religious life of the Balinese people has a vital and multifunctional role. As the main source of holy water for the people of Bali, Beji Temple must be conserved to ensure that the existence of this spring is maintained. In the process of protecting this holy water source, it is important to carry out the holy water conservation policy program in Mas Village, Ubud District, Gianyar Regency.